The prevalence of PAX2 mutations in patients with isolated colobomas or colobomas associated with urogenital anomalies. Issue 10 (October 1998) - Cunliffe, H E; McNoe, L A; Ward, T A; Devriendt, K; Brunner, H G; Eccles, M R
Abstract : The PAX2 gene is mutated in patients with ocular colobomas, vesicoureteral reflux (VUR), and kidney anomalies (renal-coloboma syndrome, OMIM 120330). The three abnormalities which make up this syndrome also occur in isolation, but the causal genes are not known. PAX2 encodes a transcription factor of the paired box class of DNA binding proteins, important for the development of the urogenital tract, optic nerve and adjacent retina, inner ear, and CNS. In this paper we have investigated the prevalence of PAX2 mutations in patients with ocular colobomas, microphthalmos, or retinal anomalies, either in isolation or with associated urogenital anomalies. Using PCR-SSCP, most or all exons of PAX2 were examined in blood DNA from 99 patients who have either ocular anomalies alone or a combination of ocular and urogenital conditions. PAX2 mutations were not detected in patients with ocular colobomas, either in isolation or with associated abnormalities, except in one patient with typical renal-coloboma syndrome. We conclude that PAX2 mutations are unlikely to be common in patients with ocular colobomas in isolation or in patients with ocular colobomas and associated anomalies, except for patients with typical renal-coloboma syndrome where PAX2 is known to be the aetiological cause.